Three new species of the genus Trachelas (Araneae: Trachelidae) from an oak forest inside the Mesoamerican biodiversity hotspot in Mexico - Rivera-Quiroz, F. Andrés; Alvarez-Padilla, Fernando (Zootaxa, 2015)
Three new species of the spider genus Trachelas L. Koch, 1872 are described and included in the speciosus group based on the following features: embolus as a separate sclerite from the tegulum with no basal coils, legs with a conspicuous fringe of long trichobothria and narrow copulatory ducts coiled irregularly. The new species described are: T. crassus sp. n., T. ductonuda sp. n. and T. odoreus sp. n. A total of 46 specimens were collected in an oak forest near Pico de Orizaba Volcano, Mexico. Most individuals were collected on low vegetation using beating trays and direct collecting at night. Additional images are available at www.unamfcaracnolab.com.